Nanocomposite coated cemented carbide tool for machining intermetallic compound / high temperature alloy and preparation method thereof

By using multi-component combinations such as lanthanum-doped tungsten carbide, modified nickel powder and boron nitride composite materials in cemented carbide tools, the problems of low bending strength, low hardness and insufficient binding force of nanocomposite coating carbide tools are solved, and its performance in intermetallic compound/high temperature alloy processing is significantly improved.

CN119346874BActive Publication Date: 2025-04-11CHENGDU OPALANG PRECISION TOOLS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411931902.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing nanocomposite coating carbide tools have low bending strength and low hardness. At the same time, the coating and matrix binding force are insufficient, which affects its application in intermetallic compound/high temperature alloy processing.

Method used

The cemented carbide matrix is ​​prepared by lanthanum doped tungsten carbide and modified nickel powder combined with other raw materials, and the coating slurry is sprayed on its surface. Boron nitride composite material and magnetic chitosan are added to the coating slurry to improve the flexural strength and hardness of the material through the combined action of multiple components, and enhance the binding force between the coating and the substrate.

Benefits of technology

The bending strength and hardness of nanocomposite coating carbide tools are significantly improved, and the bonding force between the coating and the substrate is enhanced, making it more suitable for intermetallic compound/high temperature alloy processing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of tool materials, and specifically relates to a nano-composite coated cemented carbide tool for processing intermetallic compounds / high-temperature alloys and a preparation method thereof. Intermetallic compounds / high-temperature alloys are key new materials for aircraft engines and are difficult-to-process materials. They have high red hardness, good wear resistance, and are prone to brittle fracture at high temperatures. Thermal expansion and deformation are prone to occur during processing. The present invention uses lanthanum-doped tungsten carbide and modified nickel powder in combination with other raw materials to prepare a new cemented carbide substrate, and uses boron nitride composite materials and magnetic chitosan in the coating to prepare a cemented carbide tool. Through the joint action of multiple components, the bending strength and hardness of the tool material are effectively improved, thereby enhancing the good bonding force between the coating and the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide tool materials, and in particular relates to a nano-composite coating cemented carbide tool for intermetallic compound / high-temperature alloy processing and a preparation method thereof. Background Art

[0002] The rapid rise of industry and the increasing market demand for cemented carbide tools have led to higher requirements for the performance of cemented carbide tools. As a result, cemented carbide tool surface modification technology, namely the preparation process of tool coatings, has developed. Coated tools are refractory elements or compounds with good wear resistance and high hardness coated on the surface of a substrate with high toughness, which not only improves the performance of the tool, but also broadens the scope of use of the tool. Currently, research on coated tools mainly focuses on tool coating materials, coating structures and coating preparation technologies.

[0003] A Chinese patent (publication number CN109930129B) discloses a composite diamond-coated cemented carbide tool and preparation method. The patent adjusts the internal stress of each layer of diamond coating by doping boron in the process of depositing diamond, so that the boron atoms enter the diamond lattice, thereby making the stress between different layers of nanocrystals close, effectively improving the stress distribution inside the composite coating, and further improving the integrity of the micro-nano composite coating; by doping boron elements to form boron-doped micron crystals, the cobalt element on the surface of the cemented carbide can react with it to form boron-cobalt compounds, thereby reducing the adverse effects of cobalt on the deposited diamond coating. However, the patent does not solve the problems of low bending strength and low hardness of nano-composite coated cemented carbide tools in the prior art, and the insufficient bonding strength between the coating and the substrate, which seriously affects its actual use.

[0004] Therefore, how to select a suitable cemented carbide substrate and coating slurry, and modify the key components to effectively improve the bending strength and hardness of nano-composite coated cemented carbide tools, while ensuring good bonding between the coating and the substrate so that it can be used in intermetallic compound / high-temperature alloy processing has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing and a preparation method thereof, aiming to solve the problems of low bending strength, low hardness and insufficient bonding strength between the coating and the substrate existing in the nano-composite coated cemented carbide tools in the prior art.

[0006] The present invention uses lanthanum-doped tungsten carbide and modified nickel powder in combination with other raw materials to prepare a cemented carbide substrate, and then sprays a coating slurry, and combines the boron nitride composite material and magnetic chitosan in the coating slurry to prepare a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing. Through the joint action of multiple components, the bending strength and hardness of the material are effectively improved, and good bonding between the coating and the substrate is guaranteed.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] The first aspect of the present invention provides a method for preparing a nanocomposite coated cemented carbide tool for machining an intermetallic compound / high temperature alloy, comprising the following steps:

[0009] Step S1: by weight, 50-60 parts of tungsten carbide, 30-40 parts of titanium dioxide, 4-6 parts of nickel powder and 4-6 parts of cobalt powder are mixed uniformly, placed in a hydrogen atmosphere for ball milling for 20-24 hours, and then kept warm at 1000-1020° C. for 110-120 minutes to obtain a mixed powder; the mixed powder is pressed into a green body, and the green body is subjected to a primary sintering treatment and a secondary sintering treatment in sequence to obtain a cemented carbide substrate;

[0010] Step S2: polishing the cemented carbide substrate first, then immersing it in acetone for ultrasonic infiltration treatment, and drying it naturally at room temperature after the infiltration treatment to obtain a cleaned cemented carbide substrate;

[0011] Step S3: spraying a coating slurry on the surface of the cleaned cemented carbide substrate, and then performing a sintering improvement treatment to obtain a nano-composite coating cemented carbide tool for intermetallic compound / high temperature alloy processing;

[0012] The preparation method of the coating slurry comprises: mixing 16 to 20 parts of boron nitride, 6 to 8 parts of chitosan solution and 3 to 5 parts of zirconium dioxide in parts by weight, and then ball milling for 3 to 5 hours at a rotation speed of 1200 to 1400 r / min to obtain the coating slurry;

[0013] The preparation method of the chitosan liquid comprises: adding 6-8 parts of chitosan to 200-240 parts of acetic acid solution with a mass concentration of 4% by weight, stirring and dissolving, then adding 4-6 parts of nano-iron tetroxide for ultrasonic dispersion treatment, then adding 0.2-0.4 parts of Span 80 and 20-30 parts of liquid paraffin, reacting at 50-60°C for 30-40 minutes, finally adding 0.6-0.8 parts of glutaraldehyde for cross-linking for 40-60 minutes, adjusting the pH to 9.2-9.6 after the cross-linking is completed, reacting for 2-4 hours, separating with a magnet to obtain a solid, washing the solid with acetone and deionized water in turn, and drying to obtain magnetic chitosan; adding 4-6 parts of the magnetic chitosan to 80-100 parts of acetic acid solution with a mass concentration of 2%, stirring at 40-50°C for 4-6 hours, then adding 6-8 parts of sodium lignin sulfonate and mixing evenly to obtain the chitosan liquid.

[0014] Nano-ferroferric oxide is introduced into the magnetic chitosan in the coating slurry, which can form a mechanical interlocking structure by filling the micropores, cracks and other defects on the surface of the cemented carbide substrate. This microstructure optimization not only increases the contact area between the coating and the substrate, but also enhances the mechanical locking effect and improves the bonding strength between the coating and the substrate.

[0015] As a preferred technical solution of the present invention, the conditions of the primary sintering treatment include: placing under vacuum conditions, a temperature of 880-890° C., and a time of 40-50 minutes.

[0016] As a preferred technical solution of the present invention, the conditions of the secondary sintering treatment include: placing under nitrogen protection, the temperature is 1420-1440° C., and the time is 70-80 minutes.

[0017] As a preferred technical solution of the present invention, the conditions of the ultrasonic dispersion treatment include: the ultrasonic dispersion power is 200-300W, and the ultrasonic dispersion time is 10-20min.

[0018] As a preferred technical solution of the present invention, the conditions of the sintering improvement treatment include: first keeping warm at 800-840°C for 2-4 hours, then heating to 1020-1040°C at a rate of 4°C / min for a second time for 1-2 hours, and finally heating to 1260-1280°C at a rate of 2°C / min for a third time for 2-4 hours, and cooling to room temperature after the heating is completed.

[0019] As a preferred technical solution of the present invention, the tungsten carbide is lanthanum-doped tungsten carbide; the preparation method of the lanthanum-doped tungsten carbide comprises: adding 140-150 parts of ammonium metatungstate and 10-16 parts of lanthanum nitrate to 280-300 parts of deionized water by weight, stirring for 20-30 minutes, then adding 20-25 parts of glucose, stirring for 1-2 hours and then standing for 20-24 hours to obtain a mixed liquid; spray drying and crystallization treatment of the mixed liquid to obtain a mixed precursor; first placing the mixed precursor in a nitrogen atmosphere, calcining at 460-470°C for 20-30 minutes, and then placing it in a hydrogen atmosphere, calcining at 920-940°C for 40-50 minutes to obtain the lanthanum-doped tungsten carbide.

[0020] As a preferred technical solution of the present invention, the conditions for the spray drying crystallization treatment include: the inlet air temperature of the spray drying tower is 200~210°C, the outlet air temperature is 92~94°C, the feed rate is 130~140mL / min, and the spray pressure is 1.2~1.4MPa.

[0021] The lanthanum element in lanthanum-doped tungsten carbide can act as an inhibitor in the growth process of tungsten carbide grains, preventing excessive grain growth and enhancing mechanical properties by refining the grains; at the same time, the lanthanum element can enhance the interfacial bonding between tungsten carbide particles and cobalt and nickel, and more effectively transfer stress through good interfacial bonding, preventing crack propagation, thereby improving bending strength.

[0022] As a preferred technical solution of the present invention, the nickel powder is a modified nickel powder; the preparation method of the modified nickel powder comprises: in parts by weight, 140 to 145 parts of nickel powder and 90 to 95 parts of titanium powder are mixed evenly and pressed into thin slices, the pressed thin slices are kept warm at 700 to 750°C for 3 to 4 hours, and cooled to room temperature to obtain a nickel-titanium alloy sintered material; 200 to 240 parts of the nickel-titanium alloy sintered material are placed in a ball mill, an ethanol solution with a mass concentration of 80% is added and ground for 10 to 12 hours, and dried at 100 to 110°C for 2 to 4 hours to obtain the modified nickel powder.

[0023] Modified nickel powder is composed of nickel-titanium particles. When mixed with cemented carbide and sintered at high temperature, the nickel-titanium particles will form a fine and evenly distributed second phase in the matrix. These fine particles can hinder dislocation movement, thereby increasing the bending strength of the material. At the same time, the modified nickel powder has a higher elastic modulus and can better resist deformation when subjected to bending loads, thereby maintaining a higher bending strength.

[0024] As a preferred technical solution of the present invention, the boron nitride is a boron nitride composite material; the preparation method of the boron nitride composite material comprises: adding 0.4-0.6 parts of tris(hydroxymethyl)aminomethane to 280-300 parts of deionized water and mixing them evenly, adjusting the pH to 8.4-8.6, then adding 1.2-1.6 parts of dopamine hydrochloride and stirring for 20-30 minutes, then adding 2-4 parts of hexagonal boron nitride and ultrasonically dispersing for 2-4 hours, reacting at 60-70°C for 20-24 hours, filtering, washing with deionized water, and vacuum drying to obtain modified boron nitride; adding 2-4 parts of aluminum oxide and 1-3 parts of 3-aminopropyltriethoxysilane KH550 to 80- The method comprises the following steps: stirring the mixture in 100 parts of anhydrous ethanol for 30 to 40 minutes, ultrasonically dispersing the mixture for 2 to 4 hours, then adding 8 to 10 parts of deionized water, stirring the mixture at 70 to 80° C. for 4 to 6 hours, filtering the mixture, washing the mixture with deionized water, and drying the mixture to obtain modified alumina; adding 2 to 4 parts of the modified boron nitride to 180 to 200 parts of N,N-dimethylformamide, ultrasonically treating the mixture for 50 to 60 minutes to form a suspension, and then adding 1 to 3 parts of the modified alumina, ultrasonically treating the mixture for 60 to 80 minutes, stirring the mixture at 104 to 108° C. for 6 to 8 hours, filtering the mixture after the reaction is completed, washing the mixture with deionized water, and vacuum drying the mixture to obtain the boron nitride composite material.

[0025] Both the boron nitride and alumina in the boron nitride composite material have high hardness and can form a layered structure in the microstructure. This hardness superposition effect makes the material less likely to undergo plastic deformation when subjected to high loads, thereby significantly improving the hardness. In addition, the interface bonding force between boron nitride and alumina is strong, which can effectively transfer stress when subjected to force, prevent crack expansion, and effectively improve hardness.

[0026] The second aspect of the present invention provides a nano-composite coated cemented carbide tool for machining intermetallic compound / high temperature alloy, which is prepared by the method described in the first aspect.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) Nano-iron tetroxide is introduced into the magnetic chitosan of the coating slurry of the present invention. The good metal adsorption ability of the nano-iron tetroxide interacts with the modified nickel powder with physical magnetism, so that the chitosan liquid can be well attached to the surface of the cemented carbide substrate; at the same time, when the lanthanum of lanthanum-doped tungsten carbide contacts the chitosan liquid, the lanthanum element will be partially dissolved and form lanthanum ions due to the acid contained in the liquid, and the adsorbed magnetic chitosan will complex with the lanthanum ions through the amino groups on the surface and form an interpenetrating network in the subsequent sintering process; in addition, hydroxyl and amino groups are introduced into the boron nitride composite material through trihydroxymethylaminomethane and dopamine hydrochloride, which can be combined with chitosan to form a network structure; through the synergistic effect of multiple components, the bending strength and hardness of the nano-composite coated cemented carbide tool are improved, and the bonding force between the coating and the substrate is increased.

[0029] (2) The lanthanum element in the lanthanum-doped tungsten carbide of the present invention can act as an inhibitor in the growth process of tungsten carbide grains, preventing the grains from growing excessively and enhancing the mechanical properties by refining the grains; at the same time, the lanthanum element can enhance the interface bonding force between tungsten carbide particles and cobalt and nickel, and more effectively transfer stress through good interface bonding, preventing crack propagation, thereby improving the bending strength.

[0030] (3) The modified nickel powder of the present invention is composed of nickel-titanium particles. When mixed with cemented carbide and sintered at high temperature, the nickel-titanium particles will form a fine and evenly distributed second phase in the matrix. These fine particles can hinder dislocation movement, thereby increasing the bending strength of the material. At the same time, the modified nickel powder has a higher elastic modulus and can better resist deformation when subjected to bending loads, thereby maintaining a higher bending strength.

[0031] (4) Both the boron nitride and aluminum oxide in the boron nitride composite material of the present invention have high hardness and can form a layered structure in the microstructure. This hardness superposition effect makes the material less likely to undergo plastic deformation when subjected to high loads, thereby significantly improving the hardness. In addition, the interface bonding force between boron nitride and aluminum oxide is strong, which can effectively transfer stress when subjected to force, prevent crack propagation, and effectively improve the hardness.

[0032] (5) Nano-iron tetroxide is introduced into the magnetic chitosan in the coating slurry of the present invention, which can form a mechanical interlocking structure by filling the micropores, cracks and other defects on the surface of the cemented carbide substrate. This microstructure optimization not only increases the contact area between the coating and the substrate, but also enhances the mechanical locking effect and improves the bonding strength between the coating and the substrate. DETAILED DESCRIPTION

[0033] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0034] The sources of some components in the embodiments and comparative examples are as follows:

[0035] Tungsten carbide, CAS No. 12070-13-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0036] Titanium dioxide, CAS No. 13463-67-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0037] Nickel powder, CAS No. 7440-02-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Cobalt powder, CAS No. 7440-48-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0039] Hexagonal boron nitride, CAS No. 10043-11-5, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0040] Chitosan, CAS No. 9012-76-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Sodium lignin sulfonate, CAS No. 8061-51-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Zirconium dioxide, CAS No. 1314-23-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0043] Ammonium metatungstate, CAS No. 14311-52-5, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0044] Lanthanum nitrate, CAS No. 100587-94-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Glucose, CAS No. 34620-77-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0046] Titanium powder, product number M24934, was purchased from Shanghai Myrel Biochemical Technology Co., Ltd.;

[0047] Tris(hydroxymethyl)aminomethane, CAS No. 77-86-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0048] Dopamine hydrochloride, CAS No. 62-31-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0049] Alumina, CAS No. 1344-28-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0050] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0051] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0052] N,N-dimethylformamide, CAS No. 68-12-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0053] Acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0054] Nano-ferroferric oxide, CAS No. 1317-61-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0055] Siban 80, CAS No. 1338-43-8, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0056] Liquid paraffin, CAS No. 8012-95-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0057] Glutaraldehyde, CAS No. 111-30-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0058] Acetone, CAS No. 67-64-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0059] Preparation of chitosan liquid: by weight, 8 parts of chitosan are added to 240 parts of acetic acid solution with a mass concentration of 4%, stirred and dissolved, then 6 parts of nano-ferroferric oxide are added for ultrasonic dispersion treatment (ultrasonic dispersion power is 300W, ultrasonic dispersion time is 10min), then 0.4 parts of Span 80 and 30 parts of liquid paraffin are added, reacted at 60°C for 40min, finally 0.8 parts of glutaraldehyde are added for cross-linking for 60min, after cross-linking, pH is adjusted to 9.6 and reacted for 4h, solid matter is obtained by magnetic separation, the solid matter is washed with acetone and deionized water in turn, and dried to obtain magnetic chitosan; 6 parts of the magnetic chitosan are added to 100 parts of acetic acid solution with a mass concentration of 2%, stirred at 50°C for 4h, then 8 parts of sodium lignin sulfonate are added and mixed evenly to obtain the chitosan liquid.

[0060] Preparation of lanthanum-doped tungsten carbide: In parts by weight, 150 parts of ammonium metatungstate and 16 parts of lanthanum nitrate are added to 300 parts of deionized water and stirred for 30 minutes, and then 25 parts of glucose are added and stirred for 2 hours and then allowed to stand for 24 hours to obtain a mixed liquid; the mixed liquid is spray-dried and crystallized (the inlet air temperature of the spray drying tower is 210°C, the outlet air temperature is 94°C, the feed amount is 140mL / min, and the spray pressure is 1.4MPa) to obtain a mixed precursor; the mixed precursor is first placed in a nitrogen atmosphere, calcined at 470°C for 30 minutes, and then placed in a hydrogen atmosphere, calcined at 940°C for 50 minutes to obtain the lanthanum-doped tungsten carbide.

[0061] Preparation of modified nickel powder: In parts by weight, 145 parts of nickel powder and 95 parts of titanium powder are mixed evenly and pressed into thin sheets. The pressed thin sheets are kept warm at 750°C for 3 hours and cooled to room temperature to obtain a nickel-titanium alloy sintered material. 240 parts of the nickel-titanium alloy sintered material are placed in a ball mill, an ethanol solution with a mass concentration of 80% is added and ground for 12 hours, and dried at 110°C for 2 hours to obtain the modified nickel powder.

[0062] Preparation of boron nitride composite material: add 0.6 parts of tris(hydroxymethyl)aminomethane to 300 parts of deionized water and mix well, adjust the pH to 8.6, then add 1.6 parts of dopamine hydrochloride and stir for 30 minutes, then add 4 parts of hexagonal boron nitride and ultrasonically disperse for 4 hours, react at 70°C for 20 hours, filter, wash with deionized water, and vacuum dry to obtain modified boron nitride; add 4 parts of aluminum oxide and 3 parts of 3-aminopropyltriethoxysilane KH550 to 100 parts of anhydrous ethanol and stir for 40 minutes, ultrasonically disperse for 4 hours, and react for 20 hours at 70°C. Disperse for 4 hours, then add 10 parts of deionized water, stir for 4 hours at 80°C, filter, wash with deionized water, and dry to obtain modified alumina; add 4 parts of the modified boron nitride to 200 parts of N,N-dimethylformamide for one ultrasonic treatment for 60 minutes to form a suspension, then add 3 parts of the modified alumina for a second ultrasonic treatment for 80 minutes, stir and react at 108°C for 6 hours, filter after the reaction is completed, wash with deionized water, and dry in vacuo to obtain the boron nitride composite material.

[0063] Example 1

[0064] This embodiment provides a method for preparing a nano-composite coated cemented carbide tool for machining intermetallic compounds / high-temperature alloys, comprising the following steps:

[0065] Preparation of coating slurry: By weight, 20 parts of boron nitride composite material, 8 parts of chitosan liquid and 5 parts of zirconium dioxide were mixed evenly, and then ball-milled at a rotation speed of 1400 r / min for 3 hours to obtain the coating slurry.

[0066] Step S1: in parts by weight, 60 parts of lanthanum-doped tungsten carbide, 40 parts of titanium dioxide, 6 parts of modified nickel powder and 6 parts of cobalt powder are mixed evenly, ball-milled under a hydrogen atmosphere for 24 hours, and then kept warm at 1020° C. for 110 minutes to obtain a mixed powder; the mixed powder is pressed into a green body, and the green body is subjected to a primary sintering treatment (under vacuum conditions, at a temperature of 890° C. for 40 minutes) and a secondary sintering treatment (under nitrogen protection, at a temperature of 1440° C. for 70 minutes) in sequence to obtain a cemented carbide substrate;

[0067] Step S2: polishing the cemented carbide substrate first, then immersing it in acetone for ultrasonic infiltration treatment, and drying it naturally at room temperature after the infiltration treatment to obtain a cleaned cemented carbide substrate;

[0068] Step S3: spraying the coating slurry on the surface of the cleaned cemented carbide substrate, and then performing sintering improvement treatment, first keeping it warm at 840°C for 2h, then heating it to 1040°C at a rate of 4°C / min for a second time for 1h, and finally heating it to 1280°C at a rate of 2°C / min for a third time for 2h. After the insulation is completed, cool it to room temperature to obtain a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing.

[0069] Example 2

[0070] This embodiment provides a method for preparing a nano-composite coated cemented carbide tool for machining intermetallic compounds / high-temperature alloys, comprising the following steps:

[0071] Preparation of coating slurry: By weight, 16 parts of boron nitride composite material, 6 parts of chitosan liquid and 3 parts of zirconium dioxide were mixed evenly, and then ball-milled at a rotation speed of 1200 r / min for 5 hours to obtain the coating slurry.

[0072] Step S1: 50 parts by weight of lanthanum-doped tungsten carbide, 30 parts of titanium dioxide, 4 parts of modified nickel powder and 4 parts of cobalt powder are mixed evenly, ball-milled for 20 hours under a hydrogen atmosphere, and then kept warm for 120 minutes at 1000° C. to obtain a mixed powder; the mixed powder is pressed into a green body, and the green body is subjected to a primary sintering treatment (under vacuum conditions, at a temperature of 880° C., for 50 minutes) and a secondary sintering treatment (under nitrogen protection, at a temperature of 1420° C., for 80 minutes) to obtain a cemented carbide substrate;

[0073] Step S2: polishing the cemented carbide substrate first, then immersing it in acetone for ultrasonic infiltration treatment, and drying it naturally at room temperature after the infiltration treatment to obtain a cleaned cemented carbide substrate;

[0074] Step S3: spraying the coating slurry on the surface of the cleaned cemented carbide substrate, and then performing sintering improvement treatment, first keeping it warm at 800°C for 4 hours, then heating it to 1020°C at a rate of 4°C / min for a second time for 2 hours, and finally heating it to 1260°C at a rate of 2°C / min for a third time for 4 hours. After the insulation is completed, cool it to room temperature to obtain a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing.

[0075] Example 3

[0076] This embodiment provides a method for preparing a nano-composite coated cemented carbide tool for machining intermetallic compounds / high-temperature alloys, comprising the following steps:

[0077] Preparation of coating slurry: By weight, 18 parts of boron nitride composite material, 7 parts of chitosan liquid and 4 parts of zirconium dioxide were mixed evenly, and then ball-milled at a rotation speed of 1300 r / min for 4 hours to obtain the coating slurry.

[0078] Step S1: 55 parts of lanthanum-doped tungsten carbide, 35 parts of titanium dioxide, 5 parts of modified nickel powder and 5 parts of cobalt powder are mixed uniformly by weight, ball-milled for 22 hours under a hydrogen atmosphere, and then kept warm for 115 minutes at 1010° C. to obtain a mixed powder; the mixed powder is pressed into a green body, and the green body is subjected to a primary sintering treatment (under vacuum conditions, at a temperature of 885° C., for 45 minutes) and a secondary sintering treatment (under nitrogen protection, at a temperature of 1430° C., for 75 minutes) in sequence to obtain a cemented carbide substrate;

[0079] Step S2: polishing the cemented carbide substrate first, then immersing it in acetone for ultrasonic infiltration treatment, and drying it naturally at room temperature after the infiltration treatment to obtain a cleaned cemented carbide substrate;

[0080] Step S3: spraying the coating slurry on the surface of the cleaned cemented carbide substrate, and then performing sintering improvement treatment, first keeping the temperature at 820°C for 3 hours, then heating to 1030°C at a rate of 4°C / min for a second time for 2 hours, and finally heating to 1270°C at a rate of 2°C / min for a third time for 3 hours. After the heating is completed, cooling to room temperature is achieved to obtain a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from Example 1 in that commercially available tungsten carbide is used instead of lanthanum-doped tungsten carbide, commercially available nickel powder is used instead of modified nickel powder, commercially available boron nitride is used instead of boron nitride composite material, and commercially available chitosan is used instead of magnetic chitosan to prepare chitosan solution.

[0083] Comparative Example 2

[0084] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from comparative example 1 in that lanthanum-doped tungsten carbide is used instead of commercially available tungsten carbide.

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from comparative example 1 in that modified nickel powder is used instead of commercially available nickel powder.

[0087] Comparative Example 4

[0088] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from comparative example 1 in that a boron nitride composite material is used instead of commercially available boron nitride.

[0089] Comparative Example 5

[0090] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from comparative example 1 in that magnetic chitosan is used instead of commercially available chitosan to prepare chitosan solution.

[0091] Comparative Example 6

[0092] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from Example 1 in that commercially available tungsten carbide is used instead of lanthanum-doped tungsten carbide.

[0093] Comparative Example 7

[0094] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from Example 1 in that commercially available nickel powder is used instead of modified nickel powder.

[0095] Comparative Example 8

[0096] This comparative example provides a method for preparing a coated cemented carbide tool, which differs from Example 1 in that commercially available boron nitride is used instead of the boron nitride composite material.

[0097] Comparative Example 9

[0098] This comparative example provides a method for preparing a coated cemented carbide tool, which is different from Example 1 in that commercially available chitosan is used instead of magnetic chitosan to prepare the chitosan solution.

[0099] The performance of the coated cemented carbide tool provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0100] (1) Bending strength test: Test according to the requirements of GB / T 232-2024 Metal material bending test method.

[0101] (2) Hardness test: The test was conducted by using a nano indenter (model G200, Agilent technologies, USA) using a continuous stiffness measurement method. The indenter was a diamond Berkovich tetrahedron indenter with a new indenter tip with a roundness of 20 nanometers, a maximum load of 500 mN, and a load resolution of 50 nN. The displacement resolution was less than 0.01 nm, and electromagnetic actuation was used and a capacitive sensor was used for measurement.

[0102] (3) Test of the bonding strength between coating and substrate: The bonding strength between coating and substrate was measured by a nano scratch tester (model: MST, CSM Revetest test, Switzerland). The critical load at which coating is damaged was used as the standard for measuring the bonding strength between coating and substrate. The experimental parameters were: indenter radius 200 μm, loading force 100 N, scratch rate 6 mm / min, and scratch length 3 mm.

[0103] The above performance test data is shown in Table 1.

[0104] Table 1 Performance test results

[0105] Flexural strength (MPa) Hardness (GPa) Coating-substrate bonding strength (N) Example 1 2154 36.2 88 Example 2 2137 35.4 83 Example 3 2146 35.9 86 Comparative Example 1 1879 19.8 61 Comparative Example 2 1945 20.6 64 Comparative Example 3 1938 20.3 63 Comparative Example 4 1887 24.8 66 Comparative Example 5 1892 20.8 71 Comparative Example 6 2052 30.6 77 Comparative Example 7 2064 31.3 79 Comparative Example 8 2057 30.9 78 Comparative Example 9 2071 31.8 75

[0106] From the above content, it can be seen that the present invention uses lanthanum-doped tungsten carbide and modified nickel powder in combination with other raw materials to prepare a cemented carbide substrate, and then sprays a coating slurry, and cooperates with the boron nitride composite material and magnetic chitosan in the coating slurry to prepare a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing (Example 1~Example 3), which has a bending strength of 2137~2154MPa, a hardness of 35.4~36.2GPa, and a bonding force between the coating and the substrate of 83~88N.

[0107] Compared with Example 1, commercially available tungsten carbide is used to replace lanthanum-doped tungsten carbide, commercially available nickel powder is used to replace modified nickel powder, commercially available boron nitride is used to replace boron nitride composite material, and commercially available chitosan is used to replace magnetic chitosan to prepare chitosan liquid, then the flexural strength is reduced, the hardness is reduced, and the bonding force between the coating and the substrate is reduced (Comparative Example 1); compared with Comparative Example 1, lanthanum-doped tungsten carbide is used to replace commercially available tungsten carbide, and the flexural strength is improved (Comparative Example 2); compared with Comparative Example 1, modified nickel powder is used to replace commercially available nickel powder, and the flexural strength is improved (Comparative Example 3); compared with Comparative Example 1, boron nitride composite material is used to replace commercially available boron nitride, and the hardness is increased (Comparative Example 4); compared with Comparative Example 1, magnetic chitosan is used to replace commercially available chitosan to prepare chitosan Compared with Example 1, when commercially available tungsten carbide is used instead of lanthanum-doped tungsten carbide, the flexural strength is reduced, the hardness is reduced, and the bonding strength between the coating and the substrate is reduced (Comparative Example 6); compared with Example 1, when commercially available nickel powder is used instead of modified nickel powder, the flexural strength is reduced, the hardness is reduced, and the bonding strength between the coating and the substrate is reduced (Comparative Example 7); compared with Example 1, when commercially available boron nitride is used instead of boron nitride composite material, the flexural strength is reduced, the hardness is reduced, and the bonding strength between the coating and the substrate is reduced (Comparative Example 8); compared with Example 1, when commercially available chitosan is used instead of magnetic chitosan to prepare chitosan solution, the flexural strength is reduced, the hardness is reduced, and the bonding strength between the coating and the substrate is reduced (Comparative Example 9).

[0108] In summary, the present invention uses lanthanum-doped tungsten carbide and modified nickel powder in combination with other raw materials to prepare a cemented carbide substrate, and then sprays a coating slurry, and cooperates with the boron nitride composite material and magnetic chitosan in the coating slurry to prepare a nano-composite coated cemented carbide tool for intermetallic compound / high-temperature alloy processing. Through the joint action of multiple components, the bending strength and hardness of the material are effectively improved, and good bonding between the coating and the substrate is ensured.

[0109] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a nanocomposite coated cemented carbide tool for processing intermetallic compounds / high-temperature alloys, characterized in that: The following steps are involved: Step S1: in parts by weight, 50-60 parts of tungsten carbide, 30-40 parts of titanium dioxide, 4-6 parts of nickel powder and 4-6 parts of cobalt powder are mixed evenly, roller milled for 20-24 hours, and spray granulated to obtain a mixed powder; the mixed powder is pressed into a green body, and then placed in a hydrogen atmosphere at 1000-1020° C. for 110-120 minutes, and dewaxed and pressurized and sintered in sequence to obtain a cemented carbide substrate; Step S2: polishing the cemented carbide substrate first, then immersing it in acetone for ultrasonic infiltration treatment, and drying it naturally at room temperature after the infiltration treatment to obtain a cleaned cemented carbide substrate; Step S3: spraying a coating slurry on the surface of the cleaned cemented carbide substrate, and then performing a sintering improvement treatment to obtain a nano-composite coating cemented carbide tool for intermetallic compound / high temperature alloy processing; The preparation method of the coating slurry comprises: mixing 16 to 20 parts of boron nitride, 6 to 8 parts of chitosan solution and 3 to 5 parts of zirconium dioxide in parts by weight, and then ball milling for 3 to 5 hours at a rotation speed of 1200 to 1400 r / min to obtain the coating slurry; The preparation method of the chitosan liquid comprises: adding 6-8 parts of chitosan to 200-240 parts of acetic acid solution with a mass concentration of 4% by weight, stirring and dissolving, then adding 4-6 parts of nano-iron tetroxide for ultrasonic dispersion treatment, then adding 0.2-0.4 parts of Span 80 and 20-30 parts of liquid paraffin, reacting at 50-60° C. for 30-40 minutes, finally adding 0.6-0.8 parts of glutaraldehyde for cross-linking for 40-60 minutes, adjusting the pH to 9.2-9.6 after the cross-linking is completed, reacting for 2-4 hours, separating with a magnet to obtain a solid, washing the solid with acetone and deionized water in turn, and drying to obtain magnetic chitosan; adding 4-6 parts of the magnetic chitosan to 80-100 parts of acetic acid solution with a mass concentration of 2%, stirring at 40-50° C. for 4-6 hours, then adding 6-8 parts of sodium lignin sulfonate and mixing evenly to obtain the chitosan liquid; The dewaxing pressure sintering process includes a primary sintering process and a secondary sintering process; The conditions of the primary sintering treatment include: placing under vacuum conditions, a temperature of 880-890° C., and a time of 40-50 min; The secondary sintering treatment conditions include: placing under nitrogen protection, the temperature is 1420-1440°C, and the time is 70-80 minutes; The tungsten carbide is lanthanum-doped tungsten carbide; The preparation method of the lanthanum-doped tungsten carbide comprises: adding 140-150 parts of ammonium metatungstate and 10-16 parts of lanthanum nitrate to 280-300 parts of deionized water by weight, stirring for 20-30 minutes, then adding 20-25 parts of glucose, stirring for 1-2 hours, and then standing for 20-24 hours to obtain a mixed liquid; spray drying and crystallization treatment of the mixed liquid to obtain a mixed precursor; first placing the mixed precursor in a nitrogen atmosphere, calcining at 460-470° C. for 20-30 minutes, and then placing it in a hydrogen atmosphere, calcining at 920-940° C. for 40-50 minutes to obtain the lanthanum-doped tungsten carbide; The nickel powder is modified nickel powder; The preparation method of the modified nickel powder comprises: mixing 140-145 parts of nickel powder and 90-95 parts of titanium powder uniformly by weight, pressing the mixture into thin slices, keeping the pressed thin slices at 700-750° C. for 3-4 hours, and cooling the mixture to room temperature to obtain a nickel-titanium alloy sintered material; placing 200-240 parts of the nickel-titanium alloy sintered material into a ball mill, adding an ethanol solution with a mass concentration of 80% and grinding the mixture for 10-12 hours, and drying the mixture at 100-110° C. for 2-4 hours to obtain the modified nickel powder; The boron nitride is a boron nitride composite material; The preparation method of the boron nitride composite material comprises: adding 0.4-0.6 parts of tris(hydroxymethyl)aminomethane to 280-300 parts of deionized water by weight, mixing evenly, adjusting the pH to 8.4-8.6, then adding 1.2-1.6 parts of dopamine hydrochloride and stirring for 20-30 minutes, then adding 2-4 parts of hexagonal boron nitride and ultrasonically dispersing for 2-4 hours, reacting at 60-70° C. for 20-24 hours, filtering, washing with deionized water, and vacuum drying to obtain modified boron nitride; adding 2-4 parts of aluminum oxide and 1-3 parts of 3-aminopropyltriethoxysilane KH550 to 80-100 parts of anhydrous ethanol and stirring; 30-40min, ultrasonically disperse for 2-4h, then add 8-10 parts of deionized water, stir for 4-6h at 70-80°C, filter, wash with deionized water, and dry to obtain modified alumina; add 2-4 parts of the modified boron nitride to 180-200 parts of N,N-dimethylformamide for one ultrasonic treatment for 50-60min to form a suspension, then add 1-3 parts of the modified alumina for a second ultrasonic treatment for 60-80min, stir and react at 104-108°C for 6-8h, filter after the reaction is completed, wash with deionized water, and vacuum dry to obtain the boron nitride composite material.

2. The method for preparing a nanocomposite coated cemented carbide tool for machining intermetallic compounds / high-temperature alloys according to claim 1, characterized in that: The conditions of the ultrasonic dispersion treatment include: ultrasonic dispersion power of 200-300W, and ultrasonic dispersion time of 10-20min.

3. The method for preparing a nanocomposite coated cemented carbide tool for machining intermetallic compound / high temperature alloy according to claim 1, characterized in that: The conditions of the sintering improvement treatment include: first keeping the temperature at 800-840°C for 2-4 hours, then heating to 1020-1040°C at a rate of 4°C / min for a second time of keeping the temperature for 1-2 hours, and finally heating to 1260-1280°C at a rate of 2°C / min for a third time of keeping the temperature for 2-4 hours, and cooling to room temperature after the heat preservation.

4. The method for preparing a nanocomposite coated cemented carbide tool for machining intermetallic compound / high temperature alloy according to claim 1, characterized in that: The conditions of the spray drying crystallization treatment include: the inlet air temperature of the spray drying tower is 200-210° C., the outlet air temperature is 92-94° C., the feed rate is 130-140 mL / min, and the spray pressure is 1.2-1.4 MPa.

5. Nanocomposite coated cemented carbide tool for machining intermetallic compounds / high temperature alloys, characterized in that: Prepared according to the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • A composite diamond-coated cemented carbide cutting tool and its preparation method

    CN109930129B

  • Magnetic chitosan / nano Fe3O4 composite and preparation method and application thereof

    CN102850599A

  • Metallic nickel ceramic coating with high surface hardness and manufacturing method thereof

    CN105039965A